Hubungan Teman Sebaya dan Religiusitas dengan Perilaku Seksual Beresiko pada Remaja - Nugrahmi, Mega Ade; Mariyona, Kartika; Sari, Amelya Permata; Rusdi, Pagdya Haninda Nusantri; Lailatullatifah, Nur (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the relationship between peers and religiosity with risky sexual behavior in adolescents. The research design is a cross sectional study with simple random sampling technique. This research was carried out at the Al-Kautsar Muhammadiyah Sarilamak Modern Islamic Boarding School. The sample consisted of 70 people, data collection in this study was by questionnaire, data analysis was univariate and bivariate analysis. The research that has been carried out shows that there is a significant relationship between peers and religiosity and risky sexual behavior. This means that there is a significant relationship between peers and religiosity and risky sexual behavior in adolescents. The greater the influence of peers and religiosity, the less risky sexual behavior tends to be in adolescents.